An Approach to Multi-Objective Aircraft Design - Neufeld, Daniel; Chung, Joon; Behdinan, Kamaran (Future Application and Middleware Technology on e-Science, 2009)
Aircraft design is a complex process subject to many competing disciplinary analyses and is constrained by many performance targets, airworthiness requirements, environmental regulations, and many other factors. Designers must explore a broad range of possible decisions to find the best trade-offs between many competing performance goals and design constraints while ensuring that the resulting design complies with certification and airworthiness standards. A modular Multi-Disciplinary Optimization (MDO) framework is being developed with the ability to handle multiple simultaneous objectives while considering any airworthiness constraints that can be assessed at the conceptual level. The algorithm implements a multi-objective Genetic Algorithm (GA) within an MDO framework. The problem consists of four core disciplinary analysis including structural weight estimation, aerodynamics, performance, and stability.